Quantitative analysis and evaluation of manipulation comfort of tractor gear shifting based on combined methods. Issue 4 (16th December 2018) - Xu, Hongmei; Zhong, Wenjie; Wang, Chenglong; Liu, Shuang; Liu, Haiyue; Jiang, Wei; Dong, Jiajun
Abstract: Currently, studies of the manipulation comfort of agriculturalmachinery are mainly based on qualitative analysis and subjective evaluation. This study is mainly focused on the quantitative analysis and evaluation of the manipulation comfort of tractor gear‐shifting. By taking various factors into account, a combined evaluation model and the corresponding indicator system were proposed based on the method of maximizing deviations. The data of pedal force and stroke length of the clutch were collected from eight different types of agricultural tractors, which were used as the basic data for subsequent analyses. Then, five evaluation methods, including principal component analysis (PCA), comprehensive evaluation based on the entropy, ideal solution (TOPSIS), improved TOPSIS and grey correlation analysis, were adopted to evaluate the manipulation comfort of tractor gear‐shifting. A consistency check on the evaluation results of the five methods was conducted by using the concordance coefficient method of KENDALL. Furthermore, the combined weight vector of the compatible method set was calculated by maximizing the deviations. Through comparison, we found that the evaluation results of the combined methods were consistent with the subjective evaluation results. The method of combined evaluation can compensate for the insufficiency of single methods and overcome the inconsistency of the evaluation, and thus can produce more objective and accurate results. Our results can provide references for the quantitative research of manipulation comfort of agricultural machinery equipment.